Development of an educational-methodical resource editor using Web 2.0 technologies - Гарбич-Мошора, Ольга Романівна (Eastern-European Journal of Enterprise Technologies, 2014)
Web 2.0 technologies, which correspond to the current development level of information and communication technologies and can be efficiently used in the educational activities, thereby contributing to the professional competence development and professional level improvement were reviewed and analyzed, the main benefits of the Web 2.0 technology are highlighted in the paper. Provisions on the organization of the educational process at the Drohobych Ivan Franko State Pedagogical University and syllabus are analyzed and examined. Based on this, it was concluded that much time is spent on drawing up syllabuses that must be reviewed, signed by heads of departments, deans. In this regard, the task of creating an educational-methodical resource editor that facilitates the work of teachers, saving time for filling because conventional program fields are already prescribed, checking, correction of errors is relevant. Since this editor can be placed on the Internet, the program can be filled or checked at any time regardless of the location at the moment. In developing the educational-methodical resource editor by WEB2.0 technologies - markup languages HTML, which uses hyperlinks for links and transitions from the current web page to other documents and CSS, which allows to divide the contents of the page depending on the type of document; - programming languages PHP since it provides the vast majority of hosts, is characterized by easy mastering and high speed the development of new programs and JavaScript - well suited for the implementation of interactive Ajax-based web systems and supported by all modern popular browsers; - structured query language SQL since it is characterized by high speed of operation and data processing, optimum reliability, supported by an unlimited number of users, simultaneously working with the database; - technology AJAX, in which formats JSON and XML are used for data transmission were used.